Factors affecting rural women economic empowerment in Wolaita Ethiopia - Berhanu Kuma; Abebech Godana (Cogent Economics & Finance, 2023)
Empowering rural women economically helps to ensure gender equality, the well-being of nation and the basic needs of a family. This study was conducted to figure out factors affecting rural women economic empowerment endeavors of development practitioners in Wolaita Ethiopia. Multi-stage sampling techniques were used to obtain a sample size of 100 rural households. Data were collected using cross-sectional semi-structured questionnaire, which were analyzed by descriptive and binary logit model. Rural women economic empowerment index was calculated to measure dependent variables. The index result showed that 69% of the households scored less than 0.5, and thus were considered economically not empowered. The binary logit model result revealed that age of women, marital status, educational level, perception toward economic empowerment, motivation, income, participation in decision-making and participation in leadership positively and significantly affected rural women economic empowerment. It is recommended that existing programs and strategies should be reviewed and new ones should be designed to effectively improve the situation of rural women economic empowerment.
Keywords: 330; binary logit model; rural women; women economic empowerment